Digital Marketing Strategies of Local Businesses in Competing Against Imported Smartphone Accessories in the Indonesian Market - Muhammad Dzaki Nur Hisyam; Marchyel Mahardika Wibowo; Pashya Ammar Pondaaga (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2026)
This study aims to analyze the digital marketing strategies adopted by local entrepreneurs in competing against imported smartphone accessories in the Indonesian market. The development of globalization and the rapid growth of e-commerce have facilitated the entry of imported products into the domestic market through cross-border trading systems, thereby intensifying competition especially in terms of price and product variety. These conditions require local businesses to develop adaptive and effective marketing strategies to maintain competitiveness. This study uses a qualitative descriptive approach, with data obtained through observation and literature review. The findings indicate that digital marketing strategies such as social media utilization, creation of engaging and informative content, and active consumer interaction play an important role in building trust and increasing purchase intention. Empirically, content marketing is proven to have the strongest influence on consumer purchase intention (?=0.359), followed by brand image (?=0.351) and social media engagement (?=0.209), with the model explaining 68.1% of purchase intention variance (R²=0.681). Furthermore, e-commerce adoption by local UMKM has resulted in average sales volume increases of 75%, active customer growth of 77%, and monthly revenue increases of 87%. Service differentiation including fast response, good communication, and flexibility in transaction systems also serves as a supporting factor in creating competitive advantage that imported products cannot easily replicate. Thus, digital marketing functions not merely as a promotional tool, but as a primary strategy in facing global competition.